Determination of carbamazepine and its main metabolite in human hair by capillary electrophoresis and liquid chromatography techniques, both coupled with mass spectrometry - Aneta Woźniakiewicz; Renata Wietecha-Posłuszny (Journal of Pharmaceutical and Biomedical Analysis Open)
The aim of the research was to determine carbamazepine (CBZ) and its main metabolite 10,11-epoxy-10,11-dihydro-carbamazepine (CBZ-E) in human hair using the capillary electrophoresis (CE) system coupled with mass spectrometry detection (MS) and to compare the obtained results with the liquid chromatography (LC) technique, also coupled with the MS detector. Hair samples were prepared using microwave-assisted extraction (MAE) at 60 °C for 10 min in an alkaline solution (pH = 10) with ethyl acetate as the extraction solvent. In the frame of this study, the procedure for the separation of CBZ and CBZ-E using the CE-MS technique was developed. The best results were achieved using 10 mM ammonium acetate (pH=6.8) as the background electrolyte (BGE), after filling the capillary with 1% highly sulfonated β-cyclodextrin (HSβCD) in 10 mM ammonium acetate. Then, the validation parameters of the MAE/CE-MS and MAE/LC-MS methods such as: limit of detection (for CBZ are: 0.36 and 0.22 ng/mg, respectively; for CBZ-E 0.38 and 0.17 ng/mg, respectively), limit of quantification (for CBZ are: 0.86 and 0.72 ng/mg, respectively; for CBZ-E 0.94 and 0.56 ng/mg, respectively), precision (6.91–14.5% and 2.16–15.6%, respectively), recovery (87.7–102.7% and 88.9–105.5%, respectively), and matrix effect (99.5–111.0% and 98.9–115.1%, respectively) were defined and compared. Finally, the validated methods were applied to identify and quantify carbamazepine and its metabolite in hair in patients who received CBZ for medical reasons.